Multi-metal oxide nanotube catalyst as well as preparation method and application thereof
By preparing multimetal oxide nanotube catalysts, using the combined structure of TiO2 protective layer and polymetal active center, the problem of existing catalysts being easily poisoned and inactivated in the SO2 environment is solved, significantly improving the catalyst's water and sulfur resistance and Low-temperature SCR reaction performance, suitable for industrial applications.
Patent Information
- Application Number
- CN202411465958.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The catalysts used in the existing selective catalytic reduction method have problems such as low activity, poor stability and poor sulfur resistance, especially in the SO2 environment, the catalyst is prone to poisoning and inactivation.
Using the preparation method of polymetal oxide nanotube catalyst, the hollow nanotube structure with TiO2 as a protective layer is formed by mixing tetrabutyl titanate and anhydrous ethanol, leaving it stand, drying, calcining and hydrothermal reaction, and is uniform. Distribute the polymetallic active center to enhance the anti-SO2 properties and activities of the catalyst.
It significantly improves the specific surface area of the catalyst and the low-temperature SCR reaction performance, enhances the adsorption and activation ability of NH3 and NOx, improves the water and sulfur resistance and stability of the catalyst, and is suitable for large-scale industrial applications.
Smart Images

Figure CN119259030A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst materials, and in particular to a multi-metal oxide nanotube catalyst and a preparation method and application thereof. Background Art
[0002] With the development of economy and the advancement of industrialization, the burning of fossil fuels such as coal and oil and the widespread use of industrial furnaces have led to increasingly serious air pollution problems. x It is an important environmental pollutant that will cause a series of environmental problems such as photochemical pollution and ozone layer depletion, becoming a major environmental challenge faced by countries around the world. Therefore, it is urgent to reduce NO in the atmosphere. x To be removed.
[0003] About decomposition of NO x Conventional technologies have proposed methods for controlling the temperature of the combustion furnace, methods for recirculating exhaust gas, methods for installing special burners, etc. However, the performance of these methods is poor. Since then, the selective catalytic reduction method (NH3-SCR) has been put into practical use, which has used metal oxide catalysts (V2O5-WO3 / TiO2 and V2O5-MoO3 / TiO2). However, this type of traditional catalyst has the following disadvantages: V2O5 has biological toxicity, a narrow operating temperature window (350-400°C), low selectivity under high temperature conditions, poor thermal stability and sulfur resistance. Therefore, in view of these defects, the development of new denitrification catalysts with better low-temperature activity, thermal stability and sulfur resistance has become an important direction of current research.
[0004] In recent years, nanotube materials have become an emerging research trend in the field of denitrification due to their unique hollow tubular structure and excellent physical and chemical properties. The nanotube catalysts currently studied are completed by first preparing TiO2 nanotubes and then loading active centers. Since the active centers are distributed in the outer layer, they are easily affected by the SO2 present in the flue gas, which leads to catalyst poisoning and deactivation. Therefore, how to develop a new nanotube catalyst with good anti-SO2 performance has become a problem that technicians in this field urgently need to solve. Summary of the invention
[0005] In view of this, the present invention provides a multi-metal oxide nanotube catalyst and a preparation method and application thereof, the purpose of which is to solve the technical problems of low activity, poor stability and poor sulfur resistance of the catalysts used in the existing selective catalytic reduction method.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a multi-metal oxide nanotube catalyst, comprising the following steps:
[0008] S1. Tetrabutyl titanate and anhydrous ethanol are mixed to obtain solution A; anhydrous ethanol, acetic acid, water and metal nitrate are mixed to obtain solution B;
[0009] S2, mixing solution A and solution B and allowing to stand to obtain a gel;
[0010] S3, sequentially drying, calcining and grinding the gel to obtain multi-metal oxide nanoparticles;
[0011] S4, mixing the multi-metal oxide nanoparticles, the surfactant and the alkaline solution and performing a hydrothermal reaction to obtain a reaction product;
[0012] S5. The reaction product is sequentially subjected to a first washing, an acid treatment, a second washing, centrifugation, drying and calcination to obtain a multi-metal oxide nanotube catalyst.
[0013] Furthermore, in step S1, in solution A, the mass volume ratio of tetrabutyl titanate and anhydrous ethanol is 20-30 g:10-30 mL; in solution B, the amount ratio of anhydrous ethanol, acetic acid, water and metal nitrate is 10-30 mL:10-15 mL:5-10 mL:1-5 g.
[0014] Furthermore, in step S1, the metal nitrate includes cerium nitrate and / or manganese nitrate.
[0015] Furthermore, in step S2, the temperature of the static treatment is 20 to 30° C., and the time of the static treatment is 2 to 5 days.
[0016] Furthermore, in step S3, the drying temperature is 80 to 110° C., and the drying time is 24 to 36 hours;
[0017] The calcination temperature is 500-800°C and the calcination time is 2-5h;
[0018] The particle size of the multi-metal oxide nanoparticles is 2.5-3.5 nm.
[0019] Furthermore, in step S4, the ratio of the amount of the multi-metal oxide nanoparticles, the surfactant and the alkaline solution is 1-10 g: 0.1-1 g: 50-100 mL;
[0020] The temperature of the hydrothermal reaction is 100-200° C., and the time of the hydrothermal reaction is 24-36 hours.
[0021] Further, in step S4, the surfactant includes hexadecyltrimethylammonium bromide;
[0022] The alkaline solution includes a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 5 to 15 mol / L.
[0023] Furthermore, in step S5, the acid treatment time is 12 to 24 hours; the number of centrifugation is 3 to 7 times; the drying temperature is 80 to 110° C., and the drying time is 24 to 36 hours; the calcination temperature is 500 to 800° C., and the calcination time is 2 to 4 hours.
[0024] The present invention provides a multi-metal oxide nanotube catalyst prepared by the above preparation method.
[0025] The present invention also provides application of the multi-metal oxide nanotube catalyst in ammonia selective catalytic reduction reaction.
[0026] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:
[0027] The catalyst provided by the present invention is a hollow nanotube structure formed by multi-metal oxides. TiO2 is used as a protective layer to evenly distribute the multi-metal active centers in the nanotubes, effectively avoiding the problem of active center poisoning in a SO2 environment. The formation of the nanotube structure can significantly increase the specific surface area of the catalyst and enhance its NH3 and NO x The adsorption and activation ability of the catalyst is improved, thereby promoting the NH3-SCR reaction. Compared with the existing traditional morphology catalyst, the nanotube catalyst of the present invention shows better performance in the low-temperature SCR reaction.
[0028] The preparation method of the catalyst provided by the present invention has the advantages of simple operation, low cost, significant effect, etc., and is suitable for large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The CeTiO prepared in Example 1 of the present invention x Transmission electron microscope image of the nanotube catalyst;
[0030] Figure 2 The Mn prepared in Example 2 of the present invention 0.05 Ce 0.05 TiO x Transmission electron microscope image of the nanotube catalyst;
[0031] Figure 3 The CeTiO prepared in Example 1 of the present invention x Nanoparticles and CeTiO x XRD pattern of nanotube catalyst;
[0032] Figure 4The Mn prepared in Example 2 of the present invention 0.05 Ce 0.05 TiO x Nanoparticles and Mn 0.05 Ce 0.05 TiO x XRD pattern of nanotube catalyst;
[0033] Figure 5 The CeTiO prepared in Example 1 of the present invention x Nanoparticles and CeTiO x Activity diagram of nanotube catalysts;
[0034] Figure 6 The CeTiO prepared in Example 1 of the present invention x Nanoparticles and CeTiO x N2 selectivity plot of nanotube catalysts;
[0035] Figure 7 The CeTiO prepared in Example 1 of the present invention x The anti-water and anti-sulfur activity diagram of the nanotube catalyst;
[0036] Figure 8 The Mn prepared in Example 2 of the present invention 0.05 Ce 0.05 TiO x Nanoparticles and Mn 0.05 Ce 0.05 TiO x Activity diagram of nanotube catalysts;
[0037] Fig. 9 The Mn prepared in Example 2 of the present invention 0.05 Ce 0.05 TiO x Nanoparticles and Mn 0.05 Ce 0.05 TiO x N2 selectivity plot of nanotube catalysts;
[0038] Fig.10 The Mn prepared in Example 2 of the present invention 0.05 Ce 0.05 TiO x Graph of water and sulfur resistance of nanotube catalysts. DETAILED DESCRIPTION
[0039] The present invention provides a method for preparing a multi-metal oxide nanotube catalyst, comprising the following steps:
[0040] S1. Tetrabutyl titanate and anhydrous ethanol are mixed to obtain solution A; anhydrous ethanol, acetic acid, water and metal nitrate are mixed to obtain solution B;
[0041] S2, mixing solution A and solution B and allowing to stand to obtain a gel;
[0042] S3, sequentially drying, calcining and grinding the gel to obtain multi-metal oxide nanoparticles;
[0043] S4, mixing the multi-metal oxide nanoparticles, the surfactant and the alkaline solution and performing a hydrothermal reaction to obtain a reaction product;
[0044] S5. The reaction product is sequentially subjected to a first washing, an acid treatment, a second washing, centrifugation, drying and calcination to obtain a multi-metal oxide nanotube catalyst.
[0045] In the present invention, in step S1, in solution A, the mass volume ratio of tetrabutyl titanate and anhydrous ethanol is 20-30 g:10-30 mL, preferably 22-28 g:15-25 mL, and more preferably 24-26 g:20 mL; in solution B, the amount ratio of anhydrous ethanol, acetic acid, water and metal nitrate is 10-30 mL:10-15 mL:5-10 mL:1-5 g, preferably 15-25 mL:11-14 mL:6-9 mL:2-4 g, and more preferably 20 mL:12-13 mL:7-8 mL:3 g.
[0046] In the present invention, in step S1, the metal nitrate includes cerium nitrate and / or manganese nitrate.
[0047] In the present invention, in the step S1, the mixing time is independently 5 to 15 minutes, preferably 8 to 12 minutes, and more preferably 10 minutes.
[0048] In the present invention, in step S2, the mixing time is 3 to 10 hours, the mixing is accompanied by stirring, and the stirring speed is 300 to 800 rpm, preferably 400 to 600 rpm, and more preferably 500 rpm.
[0049] In the present invention, in step S2, the temperature of the static treatment is 20 to 30°C, preferably 22 to 28°C, and more preferably 24 to 26°C; the time of the static treatment is 2 to 5 days, and preferably 3 to 4 days.
[0050] In the present invention, in step S3, the drying temperature is 80 to 110° C., preferably 85 to 105° C., and more preferably 90 to 100° C.; the drying time is 24 to 36 hours, preferably 26 to 32 hours, and more preferably 30 hours;
[0051] The calcination temperature is 500-800°C, preferably 600-700°C, and more preferably 650°C; the calcination time is 2-5h, preferably 3-4h; the heating rate from room temperature to the calcination temperature is 5-10°C / min, preferably 6-9°C / min, and more preferably 7-8°C / min.
[0052] The particle size of the multi-metal oxide nanoparticles is 2.5 to 3.5 nm, and the composition of the multi-metal oxide is M a N 0.1- a TiO x , wherein M and N are metal elements; a≤0.1, preferably a≤0.08, and more preferably a≤0.06; and the molar ratio of M+N to Ti is 1:10.
[0053] In the present invention, in step S4, the usage ratio of the multi-metal oxide nanoparticles, the surfactant and the alkaline solution is 1-10 g: 0.1-1 g: 50-100 mL, preferably 2-8 g: 0.2-0.8 g: 60-90 mL, and more preferably 4-6 g: 0.4-0.6 g: 70-80 mL;
[0054] The temperature of the hydrothermal reaction is 100-200° C., preferably 120-180° C., and more preferably 140-160° C.; the time of the hydrothermal reaction is 24-36 h, preferably 26-32 h, and more preferably 30 h.
[0055] In the present invention, in step S4, the surfactant includes hexadecyltrimethylammonium bromide;
[0056] The alkaline solution includes a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 5 to 15 mol / L, preferably 8 to 12 mol / L, and more preferably 10 mol / L.
[0057] In the present invention, in step S4, the mixing is performed by ultrasonic mixing, and the ultrasonic mixing time is 15 to 60 minutes, preferably 30 to 50 minutes, and more preferably 40 minutes.
[0058] In the present invention, the product is washed with water to neutrality in both the first washing and the second washing.
[0059] In the present invention, in the step S5, the time of the acid treatment is 12 to 24 hours, preferably 15 to 20 hours, and more preferably 18 hours; the acid solution used in the acid treatment is preferably a nitric acid solution, and the concentration of the nitric acid solution is 0.1 to 0.2 mol / L, preferably 0.12 to 0.18 mol / L, and more preferably 0.14 to 0.16 mol / L; the number of centrifugation is 3 to 7 times, preferably 4 to 6 times, and more preferably 5 times; the drying temperature is 80 to 110°C, preferably 85 to 105°C, and more preferably 90 to 100°C; the drying time is 24 to 36 hours, preferably 26 to 32 hours, and more preferably 30 hours; the calcination temperature is 500 to 800°C, preferably 600 to 700°C, and more preferably 650°C; the calcination time is 2 to 4 hours, and more preferably 3 hours; the heating rate from room temperature to the calcination temperature is 5 to 10°C / min, preferably 6 to 9°C / min, and more preferably 7 to 8°C / min.
[0060] The present invention provides a multi-metal oxide nanotube catalyst prepared by the above preparation method, wherein the particle size of the multi-metal oxide nanotube catalyst is preferably 40 to 60 meshes.
[0061] The present invention also provides application of the multi-metal oxide nanotube catalyst in ammonia selective catalytic reduction reaction.
[0062] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0063] Example 1
[0064] Weigh 22.9743 g of tetrabutyl titanate into beaker A, add 19.7 mL of anhydrous ethanol, and stir in a magnetic stirrer for 10 minutes to form solution A; weigh 2.9311 g of cerium nitrate hexahydrate into beaker B, add 7.3 mL of distilled water, 19.7 mL of anhydrous ethanol and 11.6 mL of glacial acetic acid, and stir in a magnetic stirrer for 10 minutes to form solution B.
[0065] Then, solution B was added to solution A and stirred at 500 rpm for 6 h. After being placed at room temperature for 3 days, a gel was obtained. The gel was placed in an oven at 100 °C and dried for 24 h. After being cooled to room temperature, the gel was ground in a mortar to obtain a solid powder. The solid powder was placed in a muffle furnace and heated to 500 °C at a heating rate of 5 °C / min. The solid powder was calcined at 500 °C for 4 h. After being naturally cooled to room temperature, the product was ground into powder again to obtain CeTiO x Nanoparticles.
[0066] Weigh 4.375 g CeTiO xThe nanoparticles were placed in the center of a 100 mL polytetrafluoroethylene reactor, 0.95 g of hexadecyltrimethylammonium bromide (CTAB) was added, and then 70 mL (10 mol / L) of sodium hydroxide solution was added, and the mixture was mixed evenly by ultrasonication for 30 min. The center of the reactor was transferred to a hydrothermal reactor, heated at 150 ° C in an oven for 29 h, and the product was transferred to a 300 mL beaker after natural cooling, and washed with distilled water until neutral. Then 200 mL of 0.155 mol / L nitric acid solution was added to the beaker, and the mixture was left to stand for 12 h, and then washed with water until neutral, centrifuged with water 5 times and ethanol 2 times in a centrifuge, and dried in an oven at 100 ° C for 12 h; finally, the obtained sample was placed in a muffle furnace, heated to 400 ° C at a heating rate of 5 ° C / min, calcined at 400 ° C for 2.5 h, and naturally cooled to room temperature. The product was ground, pressed into tablets, and granulated to obtain 40-60 mesh CeTiO x Nanotube catalysts.
[0067] Example 2
[0068] 22.9743 g of tetrabutyl titanate was weighed into beaker A, 19.7 mL of anhydrous ethanol was added, and the mixture was stirred in a magnetic stirrer for 10 min to form a solution A; 1.465 g of cerium nitrate hexahydrate and 1.2079 g of manganese nitrate solution (50 wt%) were placed in beaker B, 7.3 mL of distilled water, 19.7 mL of anhydrous ethanol and 11.6 mL of glacial acetic acid were added, and the mixture was stirred in a magnetic stirrer for 10 min to form a solution B.
[0069] Then, solution B was added to solution A and stirred at 500 rpm for 6 hours. After being placed at room temperature for 5 days, a gel was obtained. The gel was placed in an oven at 100°C and dried for 24 hours. After being cooled to room temperature, the gel was ground in a mortar to obtain a solid powder. The solid powder was placed in a muffle furnace and heated to 500°C at a heating rate of 5°C / min. The solid powder was calcined at 500°C for 4 hours. After being naturally cooled to room temperature, the product was ground into powder again to obtain Mn 0.05 Ce 0.05 TiO x Nanoparticles.
[0070] Weigh 4.375g Mn 0.05 Ce 0.05 TiO xThe nanoparticles were placed in a 100mL polytetrafluoroethylene reactor, 0.95g hexadecyltrimethylammonium bromide (CTAB) was added, and then 70mL (10mol / L) sodium hydroxide solution was added, and the mixture was mixed evenly by ultrasonication for 30min. The reactor core was transferred to a hydrothermal reactor, heated at 150℃ in an oven for 29h, and the product was transferred to a 300mL beaker after natural cooling, and washed with distilled water until neutral. Then 200mL of 0.155mol / L nitric acid solution was added to the beaker, and the mixture was left to stand for 18h, and then washed with water until neutral, centrifuged with water 3 times and ethanol 2 times by centrifuge, and dried in a 100℃ oven for 12h; finally, the obtained sample was placed in a muffle furnace, heated to 400℃ at a heating rate of 5℃ / min, calcined at 400℃ for 2.5h, and the product was ground, pressed into tablets and granulated after natural cooling to room temperature to obtain 40-60 mesh Mn 0.05 Ce 0.05 TiO x Nanotube catalysts.
[0071] Performance Testing
[0072] 1. TEM test
[0073] The catalytic materials were observed by transmission electron microscopy (TEM), using a Tolos, F200X, G2 model. During sample preparation, the nanotube catalyst was first placed in a centrifuge tube, anhydrous ethanol was added as a dispersant, and ultrasonic treatment was performed for 10 minutes to achieve uniform dispersion. Subsequently, a small amount of the dispersion was dripped onto the desired test material, and after it was dried at room temperature, TEM testing was performed. Figure 1 CeTiO x Transmission electron microscope image of the nanotube catalyst; Figure 2 Mn 0.05 Ce 0.05 TiO x Transmission electron microscope image of the nanotube catalyst; the TEM result shows that the catalyst material presents a nanotube shape at the microscopic level, which confirms that the present invention can successfully prepare a nanotube catalyst.
[0074] 2. XRD test
[0075] The catalyst crystal structure was analyzed by XRD using a Bruker D8 X-ray diffractometer produced by Bruker, Germany. The instrument uses Cu Kα as the radiation source, the scanning range is set to 5-80°, the acceleration voltage is 40 kV, and the scanning speed is 4° / min. The acquired XRD data was processed by Jade software to determine the crystal structure characteristics of the material.
[0076] Figure 3 The CeTiO prepared in Example 1 of the present inventionx Nanoparticles and CeTiO x XRD pattern of nanotube catalyst; Figure 4 The Mn prepared in Example 2 of the present invention 0.05 Ce 0.05 TiO x Nanoparticles and Mn 0.05 Ce 0.05 TiO x XRD pattern of nanotube catalyst; the XRD pattern results show that the materials all present anatase TiO2 phase. The formation of nanotubes reduces the peak intensity of the characteristic diffraction peak belonging to anatase TiO2, proving that the crystallinity of the catalyst is reduced, indicating that the interaction between multiple metals and Ti is increased during the formation of nanotubes.
[0077] 3. Activity, N2 selectivity and water and sulfur resistance tests
[0078] The NH3-SCR denitrification performance test was carried out in a fixed bed reactor. The reaction device consists of a heating furnace and a quartz tube reactor with an inner diameter of 6mm. During the reaction, the temperature controller adjusts the temperature of the heating furnace to control the temperature of the reactor. During the test, the screened 40-60 mesh catalyst is placed in the center of the quartz tube, quartz sand is filled in the gap, and the sample is fixed with quartz wool. The reaction gases include NH3 (1000ppm), NO (1000ppm), O2 (3vol.%), 5% H2O (for water resistance test), 100ppm SO2 (for sulfur resistance test) and N2 as the balance gas. The total gas flow rate is controlled at 200mL·min -1 , airspeed is 40000h -1 . Data collection began when the reaction temperature reached a steady state. NO conversion and N2 selectivity were calculated using the following formula:
[0079]
[0080]
[0081] Figure 5 CeTiO x Nanoparticles and CeTiO x Activity diagram of nanotube catalyst; CeTiO x The NO conversion rate of nanoparticles is close to 100% at 210-390℃. x The NO conversion rate of the nanotube catalyst was 100% at 180-390%, and the formation of nanotubes significantly improved the low-temperature activity of the catalyst.
[0082] Figure 6 CeTiO x Nanoparticles and CeTiO xN2 selectivity diagram of nanotube catalysts. The N2 selectivity of both materials is above 95% at 120-390°C, both showing excellent N2 selectivity.
[0083] Figure 7 CeTiO x The anti-water and anti-sulfur activity of nanotube catalysts; at 240℃, CeTiO x The nanotubes still have a NO conversion rate of more than 90% under the action of water and sulfur. After cutting off the supply of water and sulfur, the NO conversion rate rises back to 100%, indicating that CeTiO x Nanotube catalysts have excellent resistance to water and sulfur.
[0084] Figure 8 Mn 0.05 Ce 0.05 TiO x Nanoparticles and Mn 0.05 Ce 0.05 TiO x Activity diagram of nanotube catalysts; Mn 0.05 Ce 0.05 TiO x The NO conversion rate of nanoparticles is 100% within 210-260℃, Mn 0.05 Ce 0.05 TiO x The NO conversion rate of nanotubes is close to 100% within 180-390°C, and the formation of nanotubes significantly improves the active temperature window of the catalyst.
[0085] Fig. 9 Mn 0.05 Ce 0.05 TiO x Nanoparticles and Mn 0.05 Ce 0.05 TiO x N2 selectivity plot of nanotube catalysts; Mn 0.05 Ce 0.05 TiO x Nanoparticles have extremely poor high temperature N2 selectivity, Mn 0.05 Ce 0.05 TiO x The N2 selectivity of the nanotubes is above 95% in the entire temperature window. The formation of nanotubes significantly improves the high-temperature N2 selectivity of the catalyst.
[0086] Fig.10 The Mn prepared in Example 2 of the present invention 0.05 Ce 0.05 TiO xThe water and sulfur resistance activity diagram of the nanotube catalyst. Under the action of water and sulfur, the NO conversion rate of the nanotube is always above 95%. After cutting off the supply of water and sulfur, the NO conversion rate rises back to 100%. The surface nanotube catalyst has excellent water and sulfur resistance.
[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a multi-metal oxide nanotube catalyst, characterized in that: The following steps are involved: S1. Tetrabutyl titanate and anhydrous ethanol are mixed to obtain solution A; anhydrous ethanol, acetic acid, water and metal nitrate are mixed to obtain solution B; S2, mixing solution A and solution B and allowing to stand to obtain a gel; S3, sequentially drying, calcining and grinding the gel to obtain multi-metal oxide nanoparticles; S4, mixing the multi-metal oxide nanoparticles, the surfactant and the alkaline solution and performing a hydrothermal reaction to obtain a reaction product; S5. The reaction product is sequentially subjected to a first washing, an acid treatment, a second washing, centrifugation, drying and calcination to obtain a multi-metal oxide nanotube catalyst.
2. The preparation method according to claim 1, characterized in that: In step S1, in solution A, the mass volume ratio of tetrabutyl titanate and anhydrous ethanol is 20-30 g:10-30 mL; in solution B, the amount ratio of anhydrous ethanol, acetic acid, water and metal nitrate is 10-30 mL:10-15 mL:5-10 mL:1-5 g.
3. The preparation method according to claim 2, characterized in that: In the step S1, the metal nitrate includes cerium nitrate and / or manganese nitrate.
4. The preparation method according to any one of claims 1 to 3, characterized in that: In the step S2, the temperature of the static treatment is 20 to 30° C., and the time of the static treatment is 2 to 5 days.
5. The preparation method according to claim 4, characterized in that: In step S3, the drying temperature is 80-110° C. and the drying time is 24-36 hours; The calcination temperature is 500-800°C and the calcination time is 2-5h; The particle size of the multi-metal oxide nanoparticles is 2.5-3.5 nm.
6. The preparation method according to claim 2, 3 or 5, characterized in that: In the step S4, the ratio of the amount of the multi-metal oxide nanoparticles, the surfactant and the alkaline solution is 1-10 g: 0.1-1 g: 50-100 mL; The temperature of the hydrothermal reaction is 100-200° C., and the time of the hydrothermal reaction is 24-36 hours.
7. The preparation method according to claim 6, characterized in that: In the step S4, the surfactant includes hexadecyltrimethylammonium bromide; The alkaline solution includes a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 5 to 15 mol / L.
8. The preparation method according to claim 7, characterized in that: In step S5, the acid treatment time is 12 to 24 hours; the number of centrifugation is 3 to 7 times; the drying temperature is 80 to 110° C., and the drying time is 24 to 36 hours; the calcination temperature is 500 to 800° C., and the calcination time is 2 to 4 hours.
9. The multi-metal oxide nanotube catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the multi-metal oxide nanotube catalyst according to claim 9 in ammonia selective catalytic reduction reaction.